Odpowiedź :
Odpowiedź:
[tex]-2(4x-6y+2)=-2\cdot4x-2\cdot(-6y)-2\cdot2=\boxed{-8x+12y-4}\\\\5(-3a+2b)=5\cdot(-3a)+5\cdot2b=\boxed{-15a+10b}\\\\-4(1-5m+2n)=-4\cdot1-4\cdot(-5m)-4\cdot2n=\boxed{-4+20m-8n}\\\\6x(5xy-2y+5)=6x\cdot5xy-6x\cdot2y+6x\cdot5=\boxed{30x^2y-12xy+30x}\\\\4s(8r-s+2p)=4s\cdot8r-4s\cdot s+4s\cdot2p=\boxed{32sr-4s^2+8ps}[/tex]
Odpowiedź:
-2 ( 4x-6y +2)= -8x +12y -4
5 ( -3a + 2b)= -15 a +10b
-4 ( 1-5m +2n)= -4 +20m -8n
6x( 5xy -2y +5)= 30 x²y -12 xy +30x
4s ( 8v -s +2p)= 32vs -4s²+8 s p
Szczegółowe wyjaśnienie: